Ancient Portraiture in the Studies of Oscar Waldhauer and Mikhail Rostovtsev - Trofimova, Anna A. (Actual Problems of Theory and History of Art, 2021)
The main trends of the Russian classical studies which developed and gained its international recognition in the early 20th century. They are presented by the works of Vasilii Latyshev, Vladislav Buzeskul, Mikhail Rostovtsev, and Thaddeus Zielinski. These were historical-philological and cultural-historical studies, as well as those of social history. History of the art of antiquity represented by the names of Oscar Waldhauer, Vladimir Malmberg, Boris Farmakovsky, and Mikhail Rostovtsev evolved from description of iconography to the research of historical and artistic problems. Russia, following European countries, demonstrated gradual separation of the history of ancient art as an independent discipline from archaeology, philology, and history. A good example of this process is the research of antique portraiture. This topic became one of the key ones for Oscar Waldhauer. A student of Adolf Furtwängler and Ludwig Curtius, the representatives of German school in the late 19th and early 20th centuries, the Hermitage scholar created his sculpture catalogue based on the method of “Kopienkritik”. This method, which up to now underlies the attribution of monuments, was substantially supplemented with his studies. Logic of the research led Waldhauer to Heinrich Wölfflin’s thesis about “the history of art without names”. In the essays on the history of portrait, Waldhauer was guided by the concept that the history of art presents the history of spirit, as well as the concept of “Kunstwollen”. It was adopted by him from the works of Franz Wickoff and Alois Riegl, art historians of the Vienna School. In Waldhauer’s understanding, portrait style is an expression of “spirit of the times”. While in Germany Ludwig Curtius and Hans Delbrück adhered to a physiognomic interpretation, those who followed the Vienna school came to a conclusion that portrait had never imitated the appearance of a model. The evolution of portrait is a subject to its own laws, autonomous from social development. Another significant contribution to the study of ancient portrait, undertaken in this period was Mikhail Rostovtsev’s work, dedicated to the bust of the Bosporan Queen Dynamis. M. Rostovtsev compared attributes and symbolic signs that cover the bust with the iconography of statues of Iranian gods and rulers originating from the Nemrud Dag mound. Identification of the monument was carried out thanks to its historical interpretation. M. Rostovtsev’s discovery of the dual nature of the Bosporan monarchy, which was a symbiosis of Greek and Iranian elements, is a brilliant analysis of various historical materials that laid grounds to defining the personage. General interest in the portraiture characteristic of historiography at the beginning of the 20th century, rethinking of concepts and the search for new methods lead to several discoveries. Later, Russian historiography followed a different autonomous path. While for Western European and Anglo-American science the 20th century became the “century of portraiture”, Soviet art history returned to this topic many years later, only in 1970–1980s.
Keywords: Greek and Roman portrait; Russian historiography of ancient portrait; Oscar Waldhauer; Mikhail Rostovtsev; Russian classical studies; history of science in Russia in the 1920s; portraits of rulers in Bosporan kingdom